Is the brightness- contrast level of virtual reality videos significant for visually induced motion sickness? Experimental real-time biosensor and self-report analysis - Ugur, Emel; Konukseven, Bahriye Ozlem; Ergen, Mehmet; Aksoy, Mehmet Emin; Yoner, Serhat Ilgaz (Frontiers in Virtual Reality, 2024)
Background Virtual reality is no longer created solely with design graphics. Real life 360° videos created with special shooting techniques are now offered as open access to users’ experience. As a result, this widespread use of VR systems has increased the incidence of visually induced motion sickness. Objective In the present study, we aimed to investigate impact of brightness-contrast levels of real-life 360° videos on susceptibility to visually induced motion sickness during immersive virtual reality headset viewing. Methods In this study, 360° real-world day and night driving videos publicly available on YouTube VR were used as stimuli. Stimuli were presented in 2-min segments. Electrodermal activity was recorded throughout the stimulus presentation, and SSQ was administered immediately afterward. Results No significant difference was found between the experiments in terms of dermal activity. There is a statistically significant difference in total SSQ scores and in symptoms of fatigue, eye strain, head fullness, blurred vision, and dizziness (p < 0.005; p < 0.01) after then the night video. Conclusion The present study examined the likely impact of brightness and contrast levels in VR environments on VIMS provocation.